COLLABORATIVE PRACTICES IN WIKIPEDIA: INTERNATIONALIZATIONAND INTERCULTURALITYIN CHEMISTRY TEACHING - Silva Moretti, Andressa Algayer da [UNESP]; Barros, Daniela Melare Vieira; Souza, Aguinaldo Robinson de [UNESP] (Centro Univ Nove Julho, 2023)
Collaborative writing practices in Wikipedia occur organically by wikipedians in order to provide content the entries. In this study, the objective was to present through a case study, as an entry in Wikipedia, based on the collaborative writing practices, can be understood as an open educational resource for practices of internationalization and interculturality, in relation to scientific knowledge in Higher Education for the Teaching of Chemistry. The methodology adopted for this research was the case study according to the proposals of Ludke and Andre (1986) and, for the choice of the entry were adapted the criteria pre-established by Bolsarin (2017), adopting the entry atom analysis of excerpts from the Wikipedia page that showed evidence of content that signaled, through the collaborative writing practices, actions to promote internationalization and interculturality. This case study demonstrated that Wikipedia can function as an online tool to be used intentionally as a didactic and collaborative writing strategy by teachers aimed at providing experiences of internationalization and interculturality in classrooms, knowledge and scientific dissemination based on the principles of the concept of internationalization at home.
Keywords: chemistry teaching; internationalization; interculturality; wikipedia